Valuing recreational fishing in Tasmania and assessment of response bias in contingent valuation*. (7th January 2013) - Yamazaki, Satoshi; Rust, Steven; Jennings, Sarah; Lyle, Jeremy; Frijlink, Sven
<x xml:space="preserve">Abstract</x> We report results from contingent valuation studies in each of two Tasmanian fisheries that estimate the value of a day's recreational fishing. Published studies estimating the economic value of recreational fishing in Australia and New Zealand are limited, although the economic and social benefits associated with this activity are sizable and the importance of understanding the behaviour of recreational fishers for the sustainable management of aquatic resources is well recognised. In our contingent valuation surveys, we use a double‐bounded version of the dichotomous choice question, which improves the statistical efficiency of the estimates relative to those based on a single dichotomous choice question. We test and control for response bias, in the form of anchoring and a shift effect, that may occur in data collected using a double‐bounded dichotomous choice (DBDC) elicitation format. We highlight the importance of identifying and correcting for response bias in DBDC models on a case‐by‐case basis. Our estimation results show that there is no significant difference in the willingness to pay for a day of recreational fishing across individuals who caught different number of fish in either fishery. This suggests that high and low catch fishers placed the same value on a day's fishing.